Pemanfaatan Youtube Sebagai Penunjang Pembelajaran Daring Oleh Guru SMA Negeri 9 Ambon - Ode, Irgi; Alfredo, Ronald (Department of Communication Science, University of Pattimura, 2023)
This research is a qualitative descriptive research that aims to know the benefits of YouTube as online learning support for the teachers at State High School 9 Ambon. This research took place at State High School 9 Ambon. Napu road, Waiheru, Ambon City, Maluku. Primary data collection was carried out through interviews with various informants we involved in the use of YouTube to support online learning for teachers. The informants were State High School 9 Ambon students and teachers. The result of this research shows that State High School 9 Ambon utilizes YouTube media to achieve effective online learning, where for media presentation or explanation of material in the form of a video that is uploaded to YouTube so that the video will be distributed to students. Besides YouTube, there are several media that assist Ambon 9 State High School Teachers perform the online learning process, namely WhatsApp, Zoom, Google Meet, Classroom, and other media. It can be concluded that the use of YouTube has positive value in providing educational information that can be presented in audiovisual for so that students can observe subjects that are technical. This form of information that is presented in audiovisual form means that students can see the accuracy of the information and are not limited by space and time to access such information for free.